QUANTITATIVE CHARACTERIZATION OF CARBONATE PORE SYSTEMS ON JONGGRANGAN FORMATION USING DIGITAL IMAGE ANALYSIS (DIA) - Ari, Wibowo (Departmen Teknik Geologi, 2015)
Jonggrangan Formation is characterized by major occurrence of reef limestone and small portion of bioclastic limestone that were well exposed at Samigaluh Area, Kulon Progo Regency, Daerah Istimewa Yogyakarta Province. These carbonates have a wide variety of pore systems that imprint different petrophysical properties, which are more difficult to predict than in siliciclastics. Digital Image Analysis (DIA) can be applied to response the carbonates complexity by calculating pore value and also characterizing the pore shape in digital form. The method is based on images from rock thin sections taken under an optical microscope (OM) and also core analysis results to be compared. Sixteen rock thin section samples have been analyzed with several observation representatively in order to mitigate the effect of area selection problems. Blue-dyed liquid also has been added to those thin section samples, so the pore could be identified clearly. Based on further examination, both primary and secondary pore systems are well developed. There are six pore shapes are identified within different pore values. Crossplots of pore values indicate the pore variety depends on several rock parameters. In summary, understanding characterization of carbonate pore system on Jonggrangan Formation by using DIA method is fast and accurate, useful to encourage and enrich carbonate petrophysical analysis concept.